1206 Evaluation of a regional community-based epilepsy programme in Swaziland. Issue 3 (9th February 2012) - Bernstein, L; Ford, H; Welfare, W; Dube, B
Abstract : A community-based epilepsy service for Lubombo began in 2002. The previous hospital service had poor attendance and compliance and little active management. This study evaluated the community model. Data were collected from all patient records for April–July 2010 and key staff were interviewed. Results: 326 individuals (50% male, 37% age <20, 90% generalised seizures) attend 18 clinics. In 2009 epilepsy incidence and prevalence were 30 and 159 per 100 000, and mortality 3%. Monthly default averaged 13% in 2009 vs 23% in 2005. Monotherapy was used in 83% (phenobarbitone 56%, phenytoin 28%, carbamazepine 14%, valproate <1%), with maintenance dosage within BNF guidance in 91% and evidence of up-titration in 76%. 42% were seizure free for at least 1 year. Staff support the service on accessibility and cost for patients. Their concerns were staffing levels, supervision, training and drug supply. Patients were seen as relatively compliant with treatment, but supply problems and traditional beliefs caused some to stop. Conclusions: Swaziland's high rates of HIV (25.9% in ages 15–49) and adult mortality (620/1000 aged 15–60) affect health workers and patients; accurate record keeping is a struggle. This study shows better attendance, access to several drugs, and drug titration. Diagnosis rates are low, and seizure-free intervals could improve.